Does participation predict support for place brands? An analysis of the relationship between stakeholder involvement and brand citizenship behavior. - Ripoll González, Laura; Klijn, Erik Hans; Eshuis, Jasper; Braun, Erik (Public Administration Review, 2025)
This article studies in how far participation of stakeholders enhances their active support for place brands, conceptualized in this study as Brand Citizenship Behavior (BCB). Combining insights from governance and branding theory this article uses survey data (N = 162) among stakeholders involved in branding processes of two Dutch regions. The analysis shows that more intense participation in the development of the brand is related to more BCB. Beyond participation, perceived value of the brand for stakeholders and degree of place identity (identification with place) also positively relate to brand citizenship behavior. The findings not only confirm the importance of participation in achieving support for public brands, but also provide insight into the role of affective factors (identification) and interest‐based factors (value of the brand for the stakeholder) on BCB.